Perceived loneliness mediates the relationship between mild cognitive impairment and executive function deficits - Chenyi Chen; Valentino Marcel Tahamata; Yi-Fang Chuang; Yan-Siang Huang; Yi-Hsin Chuang; Yu-Tsen Lin; Yawei Cheng; Yang-Teng Fan; Yen-Ling Chiu; Róger Marcelo Martinez; Tsai-Tsen Liao; Ovid J. L. Tzeng (Humanities & Social Sciences Communications)
Abstract Social interaction is essential for human survival and well-being; however, aging often increases the risk of loneliness alongside cognitive changes. While research on aging has highlighted loneliness as a marker of various cognitive stages, the precise role of loneliness as a mediator of cognitive deficit in individuals with mild cognitive impairment (MCI) remains unclear. A total of 155 older adults ranging from 60 to 90 years old participated in this study, with 75 individuals diagnosed with MCI and 80 healthy controls. Outcome measures included MMSE, the Geriatric Depression Scale, and a standardized battery of neurocognitive functioning tests. In comparison to the health controls, individuals with MCI exhibited higher levels of perceived loneliness and depressive symptoms. Additionally, they demonstrated poorer performance on various neurocognitive tests. Perceived loneliness showed a positive association with depressive symptoms and a negative correlation with performance on tests assessing forward/backward digit span, vocabulary, similarity, symbol substitution, and color trails. The mediation analysis indicated that perceived loneliness significantly mediated the relationship between MCI status and executive function performance, accounting for approximately 6% of the total effect. These findings highlight the potential role of loneliness as a contributing psychosocial factor associated with cognitive performance in individuals with MCI. This understanding may inform future directions for disease monitoring and the design of targeted interventions in clinical trials addressing neurodegenerative conditions.